Cell Viability Assessment Using Fluorescence Vital Dyes and Confocal Microscopy in Evaluating Freezing and Thawing Protocols Used in Cryopreservation of Allogeneic Venous Grafts - Měřička, Pavel; Janoušek, Libor; Benda, Aleš; Lainková, Radka; Sabó, Ján; Dalecká, Markéta; Prokšová, Petra; Salmay, Myroslav; Špunda, Rudolf; Pecha, Ondřej; Jandová, Miroslava; Gregor, Jiří; et al. (International journal of molecular sciences, 2021)
The authors present their contribution to the improvement of methods suitable for the detection of the freezing and thawing damage of cells of cryopreserved venous grafts used for lower limb revascularization procedures. They studied the post-thaw viability of cells of the wall of cryopreserved venous grafts (CVG) immediately after thawing and after 24 and 48 h culture at +37 °C in two groups of six CVG selected randomly for slow thawing in the refrigerator and rapid thawing in a water bath at +37 °C. The grafts were collected from multi-organ and tissue brain-dead donors, cryopreserved, and stored in a liquid nitrogen vapor phase for five years. The viability was assessed from tissue slices obtained by perpendicular and longitudinal cuts of the thawed graft samples using in situ staining with fluorescence vital dyes. The mean and median immediate post-thaw viability values above 70% were found in using both thawing protocols and both types of cutting. The statistically significant decline in viability after the 48-h culture was observed only when using the slow thawing protocol and perpendicular cutting. The possible explanation might be the "solution effect damage" during slow thawing, which caused a gentle reduction in the graft cellularity. The possible influence of this phenomenon on the immunogenicity of CVG should be the subject of further investigations.
Keywords: Freezing; dimethylsulfoxid; Microscopy, Confocal; optické zobrazování; Optical Imaging; Humans; kryoprezervace; Dimethyl Sulfoxide; dárci tkání; Cryopreservation; Tissue Donors; Allografts; Cryoprotective Agents; Femoral Vein; vena saphena; Fluorescent Dyes; apoptóza; konfokální mikroskopie; Cell Survival; viabilita buněk; vena femoralis; Saphenous Vein; fluorescenční barviva; zmrazování; lidé; transplantace cév; Apoptosis; kryoprotektivní látky; Vascular Grafting; alografty